Solvent-Mediated Ion Pairing in Zwitterionic Systems: A Comprehensive Analysis (International Journal of Scientific Research in Science and Technology, 2024)
This study explores solvent-mediated ion pairing in zwitterionic systems, a critical phenomenon in chemical and biological processes. Using a combination of experimental and computational approaches, the research investigates how solvent polarity, hydrogen bonding, and ion-solvent interactions influence ion pairing in zwitterionic compounds. Binary solvent mixtures, specifically water and Dimethyl Sulfoxide (DMSO), are employed to analyze the role of solvation dynamics. Conductometric and spectroscopic techniques (Raman and UV-Vis spectroscopy) are used to study ion-pair stability and solvation thermodynamics across varying solvent compositions and temperatures. Computational methods, including molecular dynamics simulations, provide insights into the structural evolution of solvation shells and the thermodynamic parameters of ion pairing. Findings reveal that solvent composition critically impacts zwitterion behavior, with DMSO-rich environments favoring loose solvation shells and increased ion-pair formation. This work offers valuable insights into optimizing solvent environments for applications in pharmaceuticals, catalysis, and energy storage systems.